Government Support in Mexican Agriculture: The Program of Agri-Food Productivity and Competitiveness - Feng Wu; Ariel Soto-Caro; Zhengfei Guan (EDIS)
The Mexican government has various subsidy programs under its National Development Plan. This publication focuses on The Program of Agri-Food Productivity and Competitiveness, one of the major agricultural subsidy programs administered by the Ministry of Agriculture that subsidize economic activities in the agri-food supply chain. The publication describes the structure of the program, the subsidy rules and amounts.